2011
DOI: 10.1002/cctc.201100182
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal with a Heavy Impact: Olefin Dimerization Reactions in Triphenylbismuth Buffered Chloroaluminate Ionic Liquids

Abstract: The Supporting Information for this article contains detailed experimental procedures, preparation of the ammonium salts, ionic liquids, and complex 1, as well as a catalyst concentration series, and is available on the WWW under http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The catalytic results indicated that the mechanism of these homogeneous aluminum chloride‐based systems was similar to the mechanism we proposed for nickel‐catalyzed olefin dimerization reactions in buffered chloroaluminate ionic liquids 33. On contact with aluminum chloride, a nickel halide complex forms Ni(AlX 4 ) 2 (X=Cl, Br) species37 with weakly coordinating tetrahaloaluminate anions.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The catalytic results indicated that the mechanism of these homogeneous aluminum chloride‐based systems was similar to the mechanism we proposed for nickel‐catalyzed olefin dimerization reactions in buffered chloroaluminate ionic liquids 33. On contact with aluminum chloride, a nickel halide complex forms Ni(AlX 4 ) 2 (X=Cl, Br) species37 with weakly coordinating tetrahaloaluminate anions.…”
Section: Resultssupporting
confidence: 71%
“…Although strongly coordinating ligands, such as bidentate diimines or monodentate basic phosphines, remain at the active nickel center, the weakly coordinating [AlX 4 ] − anions can easily be replaced by olefins or buffer molecules. As no alkylating agent was present in these systems, we also assume that the catalytic cycle started with the formation of nickelacyclopentane 33…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conducting the oligomerization process of ethylene in biphasic systems allows for separating the catalyst easily from the obtained oligomer product and reusing it in recycling oligomerization processes . In addition to being used as solvents, the chloroaluminate‐type ionic liquids are also used as catalysts in the oligomerization process of ethylene …”
Section: Introductionmentioning
confidence: 99%